Stand-alone system for Oscillating Water columns: Experimental testing and comparison with numerical model (Proceedings of the European Wave and Tidal Energy Conference, 2025)
As an abundant renewable energy source, wave energy has the potential to reduce carbon emissions and diversify the energy mix. Wave energy has a comparatively low TRL compared to other renewable energy technologies. To address this issue, the industry should move towards rigorous testing, focusing on real-world testing. Utility-scale projects require significant financial resources. The use of smaller devices not intended to power the utility grid, but to test the technology and collect important data on operation and maintenance is a possible answer with a much lower cost and associated risk.This paper presents the experimental testing of the complete power-to-take-off system of a standalone floating oscillating water column equipped with a biradial turbine. The tests are conducted using the hardware that is to be assembled into the buoy. The experimental campaign includes tests, first, under steady state flow and later under variable flow conditions that mimic the sea state conditions of the buoy prototype to be deployed in the Azores, Portugal. The results are later compared with the device's numerical simulations.